2020
DOI: 10.3802/jgo.2020.31.e33
|View full text |Cite
|
Sign up to set email alerts
|

The basic principles of oncologic surgery during minimally invasive radical hysterectomy

Abstract: Patients with early cervical cancer can be treated either by surgery or by chemoradiation [1]. International guidelines recommend treatment by one oncologic modality rather than combined therapy to avoid treatment-related toxicity (European Society of Gynaecological Oncology, National Comprehensive Cancer Network) [2,3]. Consequently, pretreatment decision for one of these treatment options has to be made by an interdisciplinary tumor board council. Indeed, this recommendation reflects not only tumor-stage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Treatment method should be selected individually, but oncological carefulness has to address the vast majority [ 39 , 40 ]. Promising results of our study prove that laparoscopic surgery should not be excluded in the treatment for early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment method should be selected individually, but oncological carefulness has to address the vast majority [ 39 , 40 ]. Promising results of our study prove that laparoscopic surgery should not be excluded in the treatment for early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent minimally invasive radical hysterectomy could have shorter survival than those who underwent conventional abdominal radical hysterectomy. A possible explanation is the use of an intrauterine manipulator in minimally invasive surgery, which might increase the intrauterine pressure and spread the cancer cells into the lymphovascular space 16 19 . However, other reports showed that the use of manipulators is not associated with worse prognosis, and its clinical significance remains controversial 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental rules of oncologic surgery include the avoidance of tumor spillage and tumor manipulation and resection in tumor-free margins [ 49 ]. Techniques of MIS radical hysterectomy commonly include the use of a uterine manipulator even in patients with a visible cervical tumor, which, consequently, likely violates the above principles.…”
Section: Uterine Manipulator and Vaginal Closurementioning
confidence: 99%